Biodiversity knowledge loss in children's books and textbooks - Celis-Diez, Juan L.; Diaz-Forestier, Javiera; Marquez-Garcia, Marcela; Lazzarino, Silvia; Rozzi Marin, Ricardo Roberto; Armesto, Juan J. (My University, 2016)
Please note: The publisher is not responsible for the content or functionality of any supporting information supplied by the authors. Any queries (other than missing content) should be directed to the corresponding author for the article.
Keywords: Biodiversity; Content (measure theory); Computer science; Information loss; Information retrieval; World Wide Web; Ecology; Biology; Artificial intelligence; Mathematics